2013 IEEE 29th International Conference on Data Engineering (ICDE) 2013
DOI: 10.1109/icde.2013.6544839
|View full text |Cite
|
Sign up to set email alerts
|

Main-memory hash joins on multi-core CPUs: Tuning to the underlying hardware

Abstract: The architectural changes introduced with multicore CPUs have triggered a redesign of main-memory join algorithms. In the last few years, two diverging views have appeared. One approach advocates careful tailoring of the algorithm to the architectural parameters (cache sizes, TLB, and memory bandwidth). The other approach argues that modern hardware is good enough at hiding cache and TLB miss latencies and, consequently, the careful tailoring can be omitted without sacrificing performance. In this paper we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
286
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 206 publications
(290 citation statements)
references
References 12 publications
4
286
0
Order By: Relevance
“…Comparing sort-merge and hash join algorithms has been the topic of recent work for joins on multi-core systems and efficient algorithms for both strategies have been proposed [1,3,4,5,9,27,30]. Kim et al [27] concluded that although modern hardware currently favors hash join algorithms, future processors with wider Single-InstructionMultiple-Data (SIMD) instructions would significantly speed up sort-merge joins.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparing sort-merge and hash join algorithms has been the topic of recent work for joins on multi-core systems and efficient algorithms for both strategies have been proposed [1,3,4,5,9,27,30]. Kim et al [27] concluded that although modern hardware currently favors hash join algorithms, future processors with wider Single-InstructionMultiple-Data (SIMD) instructions would significantly speed up sort-merge joins.…”
Section: Related Workmentioning
confidence: 99%
“…As previous work [27,9,4,5,3], we investigate the join operation in isolation and do not materialize the output, i.e., we do not fetch additional data over the network after the join result has been computed. …”
Section: Input Selectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…At the time of this writing, there is active academic debate on how to parallelize the join operator on many-core architectures, with multiple sophisticated algorithms being devised and tested [17]. We can assume that the current generation of industrial systems runs less-sophisticated algorithms, and presumably in the current state may not scale linearly on many-core architectures.…”
Section: Parallelism and Concurrencymentioning
confidence: 99%